A review of the colombian snakes of the families typhlopidae and leptotyphlopidae (1944)
This review was made at the suggestion of my old friend and correspondent Hermano Nicéforo Maria, and most of the some 50 Colombian specimens examined are under his care in the Instituto La Salle, Bogotá.